Penggunaan Bahasa Slang di Media Sosial - Budiasa, I Gede; Weddha Savitri, Putu; Shanti Sari Dewi, A.A.Sg. (Humanis; Vol 25 No 2 (2021), 2021)
One of the dynamics of language use that appears on social media today is the use of slang as a reflection of current language development. This phenomenon is interesting to discuss, especially regarding the purpose of using slang or why slang is widely used when using social media. The data source for this research is the verbal form contained in the author's personal social media such as WhatsApp, Twitter and Instagram, as well as YouTube social media. The documentation method is used in data collection with note-taking techniques, especially slang words. This research is a qualitative descriptive study using the theory of Patridge (1950), which is about 15 purposes for using Slang. The results of the analysis show that slang is used for various purposes, especially as a funny ingredient, to look different and contemporary, to facilitate social relations, to reduce seriousness in conversations, to encourage deep intimacy. There are also other goals such as to present oneself, to avoid pleasantries, to show superiority, and also to do something secretive.